2017
DOI: 10.1155/2017/8378219
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin Exercise for Type 2 Diabetes Mellitus: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective To investigate the effects of Baduanjin exercise for type 2 diabetes mellitus. Methods Literature retrieval was performed in several databases, including PubMed, EMBASE, Cochrane Library, CNKI, Wanfang Data Information Site, CBM, and VIP from inception to April 2017. Randomized controlled trials on evaluating the effects of Baduanjin exercise were identified. The primary outcomes were glycosylated hemoglobin, fasting blood-glucose, and postprandial plasma glucose. Review Manager 5.2 (RevMan 5.2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…In the current study, exercise effects of the experimental group for practicing 12 weeks of Baduanjin regularly can maintain the waist-hip ratio and BMI; while the control group without exercise would increase their WHR and BMI after 12 weeks. The results are similar to previous study; Wen, et al (2017) used a systematic review of randomized controlled trials and meta-analysis to explore the benefits of Baduanjin exercise for patients with type 2 diabetes, and found that blood pressure, weight, blood glucose, and LDL were significantly reduced compared to non-intervention Baduanjin measures. (Xiong, Wang, Li, Zhang & Li, 2015).…”
Section: The Comparison Of the Changes Of Whr Bmi Hdl And Ldl (Pretsupporting
confidence: 86%
“…In the current study, exercise effects of the experimental group for practicing 12 weeks of Baduanjin regularly can maintain the waist-hip ratio and BMI; while the control group without exercise would increase their WHR and BMI after 12 weeks. The results are similar to previous study; Wen, et al (2017) used a systematic review of randomized controlled trials and meta-analysis to explore the benefits of Baduanjin exercise for patients with type 2 diabetes, and found that blood pressure, weight, blood glucose, and LDL were significantly reduced compared to non-intervention Baduanjin measures. (Xiong, Wang, Li, Zhang & Li, 2015).…”
Section: The Comparison Of the Changes Of Whr Bmi Hdl And Ldl (Pretsupporting
confidence: 86%
“…Moreover, these exercises are appreciated by the elderly and previous studies found that traditional Chinese fitness exercise can significantly improve the balance and exercise capacity of healthy people 10 and exert positive effects on patients with chronic diseases. 11 , 12 Liuzijue, featuring the combined respiratory pattern of abdominal breathing and pursed lip breathing, is performed by expiration to producing six different sounds (xu, he, hu, si, chui, and xi) together with the corresponding body movements. 9 This type of respiratory pattern can retard the expiratory flow rate and modify rapid shallow breathing patterns, thereby helping COPD patients maintain proper airway pressure, prevent premature tracheal closure, and improve gas exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Such as Baduanjin, Taijiquan, Wuqinxi, and Liuzijue. [ 13 , 22 , 23 ] However, there are few reports of traditional exercise intervention for AECOPD patients. There is no report of pulmonary rehabilitation intervention in AECOPD patients with NIV by using sitting and lying Liuzijue.…”
Section: Discussionmentioning
confidence: 99%